Studies on the bioactivities and molecular mechanism of antioxidant peptides by 3D-QSAR, in vitro evaluation and molecular dynamic simulations. Issue 4 (19th March 2020) - Yan, Wenli; Lin, Guimei; Zhang, Rong; Liang, Zhen; Wu, Wenjuan
Abstract : The bioactivities and molecular mechanism of two novel antioxidant peptides were investigated by 3D-QSAR, in vitro evaluation and MD simulations. Abstract : Two novel effective antioxidative tripeptides GWY and QWY were designed based on 3D-QSAR models. Their activities were confirmed by an improved TEAC assay. The experimental results showed that GWY and QWY possessed good antioxidant activity, equaling 3.32 mM TE and 2.97 mM TE respectively. This indicated that 3D-QSAR models possessed significant predictive capacity for drug design. In addition, molecular docking and molecular dynamics simulation were applied to reveal the potential molecular mechanism of antioxidant peptides. The result showed that GWY and QWY could enhance the stability of Keap1 by interacting with the key residues Arg415, Arg483, Arg380 and Ser555 in the active sites. Interestingly, the key residues were exactly the binding site of Nrf2 in the active pocket of Keap1. Thus, GWY and QWY could compete with Nrf2 for binding to Keap1. This demonstrated that the new tripeptides might have the ability to activate the signaling pathway Keap1–Nrf2–ARE and improve the antioxidant defense system of the body as well.